Women’s Role in Social Community and Regional Leadership in Madura: the role of women and regional leadership in Madura - Mohammad Sufiyanto; Alviatul Munawaroh; Siti Maghfiroh Qurrotul Aini (SOSHUM : Jurnal Sosial dan Humaniora, 2022)
This study discusses the role of women as regional leaders, in the East Java region precisely on the island of Madura in one period. Although initially the existence of women is also often doubted and looked at in one eye, not a few of them can answer with the achievement of very glorious achievements. Success in leading an area is not determined by its gender, but rather by the utilization of the abilities and potential possessed by the person himself. This study is qualitative descriptive, namely direct observation in four regions in the districts in Madura, with interview techniques, questionnaires, and also observations. The discussion of the role of female leaders or also called "klebun bhinik" in Madura, becomes a new marker for the existence of women themselves in social status that will be increasingly viewed. Because the position as a klebun is not only worth administrative, but also has a value of social standing. Therefore, it is not surprising that in the Madurese system that adheres to patriarchal values that are also Islamic, the role of klebun is more carried by a man. This opinion further strengthens that the position of the clergy of social value is more held by men so that the presence of klebun only continues the power that has been owned by his husband, father, or grandfather. Based on existing data can be concluded, that the existence of “klebun” in the land of Madura is indeed the successor of the previous power. They were also only administrative rulers because the real power was in the old klebun (husband, father, or grandfather) and reversed the social status in Madurese society. So it is not wrong if at the turning point women began to increase social status in the eyes of Madurese people in dynasties and power.